The Effect of Electromyography Biofeedback in Combination Conventional Physiotherapy Training on Improving Walking Speed in Individual with Chronic Stroke: A Meta-Analysis - Perdana, Suryo Saputra; Spence, Nicola; Rahayu, Umi Budi (Annual Physiotherapy Scientific Meeting Proceeding, 2022)
Background: The main important goal in rehabilitation of chronic stroke patients is improvement walking speed. EMG biofeedback training is promising treatment for improving that outcome. It offers an exceptional approach (self-control training) that does not exist in conventional physiotherapy. Based on a continuous biofeedback of EMG signal recorded in selective muscles, with the goal of modifying it. Objectives: Efficiency EMG biofeedback training in combination conventional physiotherapy approaches and the implementation into clinical settings to improve walking speed in individuals‘ chronic stroke. Methods: We searched English-language of randomised controlled studies (RCT) and words related EMG biofeedback (electromyography, biofeedback, visual biofeedback and auditory biofeedback) and related walking speed (gait speed, walking velocity, and gait velocity) as well as chronic stroke between 1980-2019 using MEDLINE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane Library, ScienceDirect, and Physiotherapy Evidence Database (PEDro), Grey Literature Report, The British Library. Results: Eleven studies including 110 participants met the inclusion criteria but only nine checked sufficient outcome data for gait speed. For this meta-analysis, the mean effect size was statistically significant (p = 0.03) with mean 2.15 (95% CI, 0.16 [0.01, 0.30]), Z test. However, the result did not exceed Minimal Clinically Important Difference (MICD) score of walking speed improvement in chronic stroke patients. Conclusions: Statistically, the result indicate that EMG biofeedback training is superior to conventional physiotherapy alone for enhancing walking speed in individuals with chronic stroke. However, the meta-analysis verified lack of clinical significance for implementing EMG biofeedback training in clinical settings. Applications/Originality/Value: This study contributes to solving nutrition problem in adolescent female athlete and as a basis for intervention in the problem of female athlete triad.